EKSPLORASI DAN SKRINING FITOKIMIA TUMBUHAN OBAT TRADISIONAL MASYARAKAT ASLI PAPUA DI DESA SAIRO DAN DESA LEBAU KABUPATEN MANOKWARI - Cecilia Maturbongs, Agatha; Ria Dwi Natalia Sianipar, Fajar; Serio, Rita (Universitas Cokroaminoto Palopo, 2024)
Indigenous Papuans utilize plants around them for traditional medicine. This study aims to determine the types of traditional medicinal plants used by indigenous Papuans in Sairo Village and Lebau Village, as well as the content of secondary metabolites of these plants to enrich pharmacological data. The method used was interviews and field surveys followed by phytochemical screening to determine the content of compounds in plants used as medicine. The results obtained in this study are 27 types of medicinal plants used by indigenous Papuans in in Sairo Village and Lebau Village of Manokwari Regency. Plant parts are utilized and the way they are used varies for various diseases. The results of phytochemical screening show that there are saponins, alkaloids and tannins that vary in medicinal plants.